Penerapan Geobag di Daerah Sempadan Sungai Krueng Langsa Sesi Desa Meurandeh Aceh Dalam Penanggulangan Erosi - Fauzia, Arisna; Wilanda, Denova; Nufus, Chairun (Civil Infrastructure Engineering and Architectural Design, 2025)
The Krueng Langsa River in Aceh often faces landslide problems due to natural erosion, human activities, and changes in river flow. This study aims to design a landslide mitigation system using geobags as a control technology on the Krueng Langsa Riverbank. Geobags, bags made of geotextiles filled with materials such as sand, are systematically installed to reinforce river banks. Primary data was obtained through field surveys, while secondary data was taken from related stakeholders, including regional maps and elevation data. The results of the study show that the installation of geobags along the 295 meters of the Krueng Langsa River bank can reduce the risk of landslides. The total calculation of the need for geobags reaches 9,440 units, which are designed to withstand flooding and strengthen cliff structures. In conclusion, geobags are an effective temporary solution in resisting erosion and waterlogging. This study recommends the development of permanent infrastructure for sustainable landslide control.